EP.WE.690PPI Prescribing in Vascular Discharges. (28th October 2021) - Hooper, Amy; Cheung, Fang Yi; Murray, Anna
Abstract: Aims: Aspirin and clopidogrel are ubiquitously seen in prescriptions of most attendees to hospitals, especially those being admitted to a vascular unit. Most, if not all, are on at least one anti-platelet agent, and some are on dual antiplatelets (DAPA) or an anticoagulant. These increase the risk for upper gastrointestinal (UGI) bleeds, which lead to significant morbidity and mortality. In order to prevent this, proton pump inhibitors (PPIs) are recommended to be prescribed for patients with increased risk of UGI bleeds. Our aim for this audit was to evaluate the prescription of PPIs in vascular patients discharged from a major vascular hub. Methods: Data was collected from a prospectively maintained database of consecutive primary vascular discharges between 01/09/2020 and 31/09/2020. Results: 87 patients discharged in this period (71% Male, Median age 72 (22-92) yrs). 26% of admissions accounted for Diabetic foot infection management, 25% for Critical Limb Ischaemia management and 20% for Thoracic or Aortic Aneurysm management. 70% of patients were discharged with either a single or DAPA. 94% of patients met the NICE guideline for requirement for a PPI. 49% of those patients were not discharged with a PPI. Of the patients who should have been prescribed a PPI on discharge, 5% suffered UGI bleeds in the follow up period (2/42). Conclusions: PPIs are often not prescribed when discharging vascular patients, most of whom are high risk for having UGI bleeds. We will re-audit this after education and protocols have been implemented.